2013
DOI: 10.1080/09540121.2013.859650
|View full text |Cite
|
Sign up to set email alerts
|

Gender and risk behaviors for HIV and sexually transmitted infections among recently released inmates: A prospective cohort study

Abstract: Women in prison have a higher prevalence of HIV than men. After release from prison, former inmates have the opportunity to engage in risk behaviors for HIV and other sexually transmitted infections (STI). We sought to assess change in risk behaviors over time and the association of gender with risk behavior in the post-release period. In this prospective cohort study, we interviewed 200 former inmates (51 women) approximately 2 weeks (baseline) and 3 months (follow-up) after release and tested them for HIV in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 36 publications
1
22
0
Order By: Relevance
“…13,18-20 The literature also shows that the risk of death, drug use, overdose, and HIV are great for both women and men in the days and weeks immediately after release from jail or prison. 19,21,22 The few studies of women's priorities after release from jail reflect the reality of logistical barriers to reentry success, though do not highlight women's acknowledgment of these dangerous post-release health outcomes. 13,14 We also found little evidence that women's priorities mirrored the reality of poor post-release health outcomes documented in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13,18-20 The literature also shows that the risk of death, drug use, overdose, and HIV are great for both women and men in the days and weeks immediately after release from jail or prison. 19,21,22 The few studies of women's priorities after release from jail reflect the reality of logistical barriers to reentry success, though do not highlight women's acknowledgment of these dangerous post-release health outcomes. 13,14 We also found little evidence that women's priorities mirrored the reality of poor post-release health outcomes documented in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 We also found little evidence that women's priorities mirrored the reality of poor post-release health outcomes documented in the literature. 19,21,22 The distinction between a woman's real health risks after jail and her priorities is important – ultimately, her set of priorities will drive her actions. 16 The alignment of risks, priorities, and reentry realities for women could be examined further in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies found that men engage in higher rates of drug-related HIV risk behavior in comparison with women; others showed that women are more likely to engage in transactional and unprotected sex. (Oser et al 2006; Binswanger et al 2014; Khan et al 2008; L. M. Adams et al 2013). These studies have primarily focused on individual risk behaviors, with few exploring how specific factors mediate increased risk for HIV by gender.…”
Section: Introductionmentioning
confidence: 99%
“…This study is a secondary analysis of data that was originally collected to examine the HIV risk behaviours of people recently released from prison (Binswanger, Mueller, Beaty, Min, & Corsi, 2014). The original study was a prospective cohort study of people released from a western state prison system to a single metropolitan area.…”
Section: Methodsmentioning
confidence: 99%